Teacher Shortages in Kansas and in the Nation - Kenneth A. Weaver; Rudy Perez (The Advocate, 2016)
In March, 2016, Kansas Commissioner of Education Randy Watson created the Blue Ribbon Task Force on Teacher Vacancies and Supply. The authors of this article were task force co-chairs. This article reports the key finds of the task force and then reports current research findings about teacher shortage from across the nation. We then list recommendations for teacher educators to improve the supply of teachers and retention of career teachers. The conclusion crystallizes the four challenges Kansas has to increase the number of teachers in the state.